Consistency of International Classification of Diseases-10 ICD-10 and the Causes of Death Written in the Death Certificates in Uludağ University Medical Faculty Hospital - Aydıner, Ahmet Hüsamettin; Fedakar, Recep (The Bulletin of Legal Medicine, 2006)
Registries for the causes of death constitute one of the basic data of health system. In this study, we aimed to evaluate the consistency of International Classification of Diseases-10 (ICD-10) and the causes of death written in the death certificates of the State Statistics Institute in Uludağ University Medical Faculty Hospital death certificates. There were a total of 4043 recorded death certificates between the years 2003 and 2005. Data were arranged according to age, sex, clinic, cause or causes, and time of death. Thereafter, codes were found in the ICD-10 book according to the causes of death. The cases were arranged into three groups in respect of the accuracy of the cause of death. Of the total 4043 cases, correct death cause were written in majority (n = 3519, %87,0) of the cases. The deaths were attributed to the disease terms not available in the ICD-10 lists or condition of terminal phases such as cardio-respiratory arrest in 524 (13%) cases. However, while the cause of death was written in certificates, in majority it was defined either with unspecified diseases or addition of the findings of terminal phases to death cause. In order to improve the correctness of reporting the causes of death, the informative education of the physicians and composing the configuration and contents of the forms as to prevent from the potential remissness and forgetfulness could be useful. Key words: Cause of death, ICD-10, death certificate